Offer to do the fire protection coating at increased quantity of BOQ item no.10.2 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding offer to do the fire protection coating at increased quantity of BOQ item no. 10.2 of BRAC University new campus project.